Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Outgoing Fresno County Bar Association President Robert Oliver giving thanks for the gift of a wall clock with brass plate; President-elect Rodney Worrel looking on 5080 E. Kings Canyon Road, Fresno